2018
DOI: 10.1111/jog.13644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pregnancy outcomes and the incidence of fetal congenital abnormalities in infertile women treated with letrozole and clomiphene citrate

Abstract: Based on the findings of this study, it seems that the incidence of congenital anomalies in offspring after OI with letrozole is not increased compared to the CC group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Our study followed pregnancy outcomes, and no fetal anomalies were documented in our study group, supporting the safety of letrozole [38][39][40][41][42]. Our study patients did not demonstrate any significant differences in pregnancy complications in either the aFET or the letrozole group.…”
Section: Afet Vs Ovu-fetsupporting
confidence: 72%
“…Our study followed pregnancy outcomes, and no fetal anomalies were documented in our study group, supporting the safety of letrozole [38][39][40][41][42]. Our study patients did not demonstrate any significant differences in pregnancy complications in either the aFET or the letrozole group.…”
Section: Afet Vs Ovu-fetsupporting
confidence: 72%
“…The current meta-analysis includes 4 RCTs [ 17 20 ] and 2 non-randomized controlled trials (NRCTs), [ 21 , 22 ] their evaluation of quality are judged by 2 methods, RCT is according to the Cochrane Handbook, NRCT is on the basis of the Newcastle–Ottawa Scale. In the Cochrane Handbook we use low, high or unclear to assess the quality in 7 fields which are consist of random sequence generation, allocation concealment, blinding of participants and personnel, blinding of outcome assessment, incomplete outcome data, selective outcome reporting and other sources of bias.…”
Section: Methodsmentioning
confidence: 99%
“…Six studies that contain 3413 participants all reported the total rate of pregnancy. Study Akbarisene [ 21 ] and Khanna [ 22 ] belong to NRCTs, therefore, we set a subgroup to further analyze. The result suggested that there was no significant difference between the 2 groups (RR= 1.06, I 2 = 11%, P = .38).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations